Penegakan Hukum Kasus Tindak Pidana Korupsi Oleh Forkot Lembaga Swadaya Masyarakat LSM Kabupaten Natuna : (Studi Kasus Putusan Nomor 28/Pid.Sus-TPK/2023/PN Tpg) - Juni Sukarta; Muhamad Fathur Rahman Bey Husdi; Heni Widiyani (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
The Latin word "corruption" comes from the words "korruptus" and "corruption", which means "bad, depraved, deviant from morals, insulting words, or slanderous. Corruption, according to the Black Law Dictionary, is defined as an action carried out with the aim of obtaining several benefits which are contrary to duties and other official truths: "an act from an official or trusted person who unlawfully and wrongly uses a number of advantages for himself or another person which is contrary to his duties and other truths". Eradication of Corruption Crimes Number 31 of 1999, which was later changed to Law Number 20 of 2001, shows that the government is committed to eliminating criminal acts of corruption. The author uses standard methods in writing this journal to describe the problems discussed: Law Enforcement in Criminal Cases Corruption of the Natuna Regency NGO Non-Governmental Organization Forkot (Case Study Decision Number 28/Pid.sus-TPK/2023/PN Tpg). They use data from various reading sources, such as statutory regulations, books, and the same decisions. The criminal act of corruption committed by Forkot NGO Natuna, led by Wan Sofian Telang, violates Article 11 of Law Number 20 2001 concerning amendments to law number 31 of 1999 concerning the eradication of criminal acts of corruption in conjunction with article 15 and article 56 1 of the Criminal Procedure Code.